The frequency of work related-stress among physical therapists of Pakistan–an online survey - Muhammad Waqas Ghauri; Arslan Saeed; Tahir Mahmood; Komal Tariq (Journal of University Medical & Dental College, 2023)
BACKGROUND & OBJECTIVE: Job related stress an important predictor of quality of work among health care professionals. The stress can affect the efficiency and capability of a working team. The objective of this study was to determine the work-related stress among physical therapists from different regions of Pakistan. METHODOLOGY: This was a cross sectional study having 264 participants after ethical approval from June 2020 to November 2020. The data was collected using convenient sampling technique. Physical therapist from the age range of 25 to 50 years old, both genders, with at least 2 years of clinical or teaching experience who were actively employed in either the public or private sector without a break were included. Data was collected through an online questionnaire “stress evaluation questionnaire for health care provider”. Microsoft Excel and SPSS Version 21 were used to present and analyze data. RESULTS: A total of 264 physical therapists from different regions of Pakistan participated in this study. Out of them 56% were males and 44% were females with a mean age of 34.5+ 9.5 and 31.5+ 8.5 respectively. From these, 38% of physical therapists were employed in academic organizations while 62% were working in clinical setups. Out of these, 211 (80%) participants were satisfied with their job but 57.6% of these participants had mild level of stress, while 14.4% had moderate stress and 2.7% had severe stress with p-value = 0.295. There was no difference observed in work related stress in male and female. CONCLUSION: The study concluded that 7.6% participants had mild, 14.4% had moderate and 2.7% had severe level of work related-stress.